2023
DOI: 10.1002/bdr2.2275
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of school and cognitive function domains of health‐related quality of life measures for children and young adults with congenital heart disease

Chrysovalanto Mamasoula,
Lindsay Pennington,
Adenike Motunrayo Adesanya
et al.

Abstract: BackgroundResearch on cognitive and school functioning domains of health‐related quality of life (HRQOL) for children and adolescents with congenital heart disease (CHD) presents inconsistencies.ObjectivesTo summarize and synthesize data on school and cognitive function domains of HRQOL for children and young people (CYP) with CHD.MethodsFive electronic databases MEDLINE, Scopus, PsycINFO, EMBASE, ERI, and citations were systematically searched. We included original‐research articles reporting the cognitive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(345 reference statements)
0
0
0
Order By: Relevance
“…A recent systematic review (Mamasoula et al, 2024) of cognitive and school function domains of healthrelated quality of life (QoL) measures for children and young adults with CHD was able to identify 34 related studies. However, the review revealed several major limitations in these studies: (1) Most of the published QoL studies included cohorts that were predominantly composed of teenagers or young adults with CHD.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review (Mamasoula et al, 2024) of cognitive and school function domains of healthrelated quality of life (QoL) measures for children and young adults with CHD was able to identify 34 related studies. However, the review revealed several major limitations in these studies: (1) Most of the published QoL studies included cohorts that were predominantly composed of teenagers or young adults with CHD.…”
Section: Introductionmentioning
confidence: 99%